The Government's Role in Legal Protection of Workers on Fixed-Time Employment Agreements in the Context of Boycotting Pro-Israel Products - Yasmine Putri Andrian; Tri Sulistiyono; Shinta Widi Deswinta (PATTIMURA Legal Journal, 2025)
Introduction: Boycotts of products associated with support for Israel can have an impact on business and employment, especially for workers with Fixed-Time Employment Agreements. Purposes of the Research: This study discusses the role of the government in providing legal protection for Fixed-Time Work Agreement workers in the midst of the boycott, with a case study on Starbucks Coffeeshop in Semarang City. The phenomenon of boycotts often affects the sustainability of the business and the stability of the workforce, especially Fixed-Time Employment Agreements workers who are more vulnerable to Termination of Employment. Methods of the Research: This study uses an empirical juridical method with a qualitative approach, examining labor regulations and the implementation of legal protection policies for Fixed-Time Work Agreements workers in situations of business uncertainty due to boycott actions. Results Main Findings of the Research: The results of the study show that labor regulations have regulated protections for Fixed-Time Work Agreement workers, including the right to compensation upon termination of employment. However, there is still room for improvement, especially in the aspect of supervision and law enforcement, so that every Fixed-Time Work Agreement worker can obtain his rights fairly and in accordance with applicable regulations. The government has a strategic role in ensuring that workers' rights remain protected, both through labor policies, industrial relations mediation, and the provision of legal aid for workers affected by Termination of Employment. The study recommends strengthening regulations and oversight to ensure more effective protections for Fixed-Time Employment Agreements workers amid the impact of boycotts on the employment sector.